The use of the female voice in three novels by J.M. Coetzee - Graham, Lucy Valerie (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1997)
This study investigates J.M. Coetzee's use of the female voice in In the Heart of the Country, Foe and Age of Iron, and is based on the premise that Coetzee's position as a male author using a female voice is important for readings of these novels. Although the implications of Coetzee's strategy are examined against the theoretical background of feminist or gender-related discourses, this study does not attempt to claim Coetzee for feminism, nor to prove him a misogynist. Instead, it focuses on the specific positional and narrative possibilities afforded by Coetzee's use of a female voice. Chapter One comments on the fact that Coetzee's strategy of "textual cross-dressing" has not been given much critical attention in the past, observing that research on South African literature has largely been limited to studies of racial and colonial problematics. This introductory chapter mentions that the different female narrators in Coetzee's novels articulate aspects of a discourse in crisis, resulting in profound ambivalence in their representation. Chapter Two observes that the female voices in Coetzee's novels invoke the textual illusion of a speaking/writing female body, and explains that this is useful in expressing aspects of what Coetzee refers to as the suffering body. Although Coetzee appropriates a female narrative position and employs certain subversive textual elements associated with "the feminine", attempts made by certain critics to label Coetzee's writing as ecriture feminine are rejected as highly problematic. Instead, the study contends that the femaleness of the narrators relative to "masculine" discursive power enables Coetzee to perform a critique of power "from a position of weakness". Furthermore, the presence of certain "feminine" elements within these narrators suggests Coetzee's affiliation with characteristics derided within phallocratic discourses, and becomes a strategic means of fictive self-positioning, of figuring his own position as a dissident. Chapter Three is a study of In the Heart of the Country, and proposes that Magda is represented as a typical nineteenth century hysteric. Her hystericized narrative is linked to certain avant-garde narratives, such as the nouveau roman and "New Wave" cinematography, both cited by Coetzee as influences on the novel. Furthermore, the novel provides insight into the ambiguous role of the hysteric and dramatises the position of the dissident: on a discursive level Magda's narrative is subversive, and yet in terms of social "reality" her revolt is ineffectual. Chapter Four addresses the issue of author-ity in Foe, and draws on Coetzee's affiliation with Susan Barton, the struggling authoress, whose narrative reveals the levels of power and authority operating within, novelistic discourse when she asks "Who ,is speaking me?". The study observes that Foe also performs a critique of the power-seeking project of liberal feminism, as the novel sets Susan's quest for authorship against the background of a more radical "otherness", that of Friday. Chapter Five asserts that Age of Iron exploits the ethical possibilities of a maternal discourse. Tracing parallels between images of motherhood in psychoanalytic feminism and in Age of Iron, this chapter argues that Kristeva's theory of abjection is relevant for a reading of Elizabeth Curren's position as a mother who has cancer. The childbirth metaphor as it appears in Age- of Iron becomes an alternative and profoundly ethical way of figuring the process of novel writing.
Keywords: Coetzee, J. M., 1940- -- Criticism and interpretation; Coetzee, J. M., 1940- Foe; Coetzee, J. M., 1940- In the heart of the country; Coetzee, J. M., 1940- Age Of Iron; Women in literature; Voice in literature